O debate sobre desigualdade de gênero no discurso de adjudicação - Garcez, Lucas Nogueira (2016)
This work is intended to contribute to the literature about judiciary legitimacy and legal reasoning. The study utilizes empirical evidence from a gender discrimination related cases sample.